2005
DOI: 10.1172/jci22760
|View full text |Cite
|
Sign up to set email alerts
|

A novel COL1A1 mutation in infantile cortical hyperostosis (Caffey disease) expands the spectrum of collagen-related disorders

Abstract: Infantile cortical hyperostosis (Caffey disease) is characterized by spontaneous episodes of subperiosteal new bone formation along 1 or more bones commencing within the first 5 months of life. A genome-wide screen for genetic linkage in a large family with an autosomal dominant form of Caffey disease (ADC) revealed a locus on chromosome 17q21 (LOD score, 6.78). Affected individuals and obligate carriers were heterozygous for a missense mutation (3040C→T) in exon 41 of the gene encoding the α1(I) chain of type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
73
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(77 citation statements)
references
References 46 publications
4
73
0
Order By: Relevance
“…However, DIRA syndrome shows no response to antibiotic therapy, and steroids have little to no impact on disease progression. The findings of diffuse periostitis involving the long bones, not present in this case but seen in 8/9 patients in Aksentijevich's report, simulate Caffey's disease although Caffey's disease is self-limited and caused by an autosomaldominant mutation of COL1A1 [3]. Furthermore, DIRA has not been shown to involve the mandible.…”
Section: Discussionmentioning
confidence: 47%
“…However, DIRA syndrome shows no response to antibiotic therapy, and steroids have little to no impact on disease progression. The findings of diffuse periostitis involving the long bones, not present in this case but seen in 8/9 patients in Aksentijevich's report, simulate Caffey's disease although Caffey's disease is self-limited and caused by an autosomaldominant mutation of COL1A1 [3]. Furthermore, DIRA has not been shown to involve the mandible.…”
Section: Discussionmentioning
confidence: 47%
“…The sequencing of exon 41 of COL1A1, as described by Gensure et al, confirmed the heterozygous mutation c.3040 C>T (p.R1014C) in the proband [1]. The mother was not found to carry this mutation.…”
Section: Case Reportmentioning
confidence: 55%
“…Both familial and sporadic occurrences have been reported. The familial autosomal dominant form has now been found to be a collagenopathy caused by a single heterozygous missense mutation in COL1A1 (c3040C>T; p R1014C) [1][2][3][4]. Though there are several case reports of Caffey disease from India, no data regarding their genetic mutation pattern have been published.…”
Section: Introductionmentioning
confidence: 99%
“…Most cases are sporadic but an autosomal dominant inheritance with limited penetrance has been reported [3,4]. More recently, Gensure et al [5] identified a heterozygous mutation of the gene encoding for the alpha1(I) chain of type I collagen (COL1A1) on chromosome 17q in a large family with an autosomal dominant form of Caffey's disease.…”
Section: Discussionmentioning
confidence: 99%